Exopolysaccharide Produced by Pediococcus pentosaceus E8: Structure, Bio-Activities, and Its Potential Application - Jiang, Guangyang; He, Juan; Gan, Longzhan; Li, Xiaoguang; Xu, Zhe; Yang, Li; Li, Ran; Tian, Yongqiang (Frontiers in Microbiology, 2022)
The novel exopolysaccharide EPS-E8, secreted by P. pentosaceus E8, was obtained by anion-exchange and gel filtration chromatography. Structural analyses identified EPS-E8 as a heteropolysaccharide containing mannose, glucose, and galactose. Its major backbone consists of→2)-α-D-Manp-(1→2,6)-α-D-Glcp-(1→6)-α-D-Manp-(1→, and its molecular weight is 5.02 × 104 g/mol. Using atomic force microscopy and scanning electron microscopy, many spherical and irregular reticular-like shapes were observed in the microstructure of EPS-E8. EPS-E8 has outstanding thermal stability (305.7 °C). Both the zeta potential absolute value and average particle diameter increased gradually with increasing concentration. Moreover, at a concentration of 10 mg/ml, the antioxidant capacities of DPPH, ABTS and hydroxyl radical were 50.62 ± 0.5%, 52.17 ± 1.4%, and 58.91 ± 0.7%, respectively. EPS-E8 possesses excellent emulsifying properties against several food-grade oils, and its activity is retained under various conditions (temperature, pH, and ionic strength). Finally, we found that EPS-E8 as a polysaccharide-based coating could reduce the weight loss and malondialdehyde (MDA) content of strawberry, as well as preserving the vitamin C and soluble solid content during storage at 20 °C. Together, the results support the potential application of EPS-E8 as an emulsifier, and a polysaccharide-based coating in fruit preservation.